Imagination and the meaningful brain - Modell, Arnold H. (Cambridge, Mass. : MIT, 2006)
1. Uncertain Steps toward a Biology of Meaning## 2. Metaphor, Memory, and Unconscious Imagination## 3. Imagination’s Autonomy## 4. The Corporeal Imagination## 5. Intentionality and the Self ##6. Directing the Imagination## 7. The Uniqueness of Human Feelings ##8. Feelings and Value## 9. Imagining Other Minds ##10. Mirror Neurons, Gestures, and the Origins of Metaphor ##11. Experience and the Mind-Body Problem193
"A Bradford book". Originally published: 2003.
boek